2017
DOI: 10.1177/0020731416689549
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Payer and Racial/Ethnic Mix at Private Academic Medical Centers in Boston and New York City

Abstract: Academic medical centers (AMCs) are widely perceived as providing the highest-quality medical care. To investigate disparities in access to such care, we studied the racial/ethnic and payer mixes at private AMCs of New York City (NYC) and Boston, two cities where these prestigious institutions play a dominant role in the health care system. We used individual-level inpatient discharge data for acute care hospitals to examine the degree of hospital racial/ethnic and insurance segregation in both cities using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 20 publications
1
32
0
1
Order By: Relevance
“…This discordance in care by facility type is important as numerous studies have shown that access to academic facilities is limited and is dependent on race/ethnicity, median income, insurance type, and geographic location 32,33 . In a multivariable regression study utilizing hospital discharge records, Tikkanen et al 34 showed that Black patients were 2‐3 times less likely to be hospitalized in an academic facility compared to White patients. Additionally, uninsured patients were five times less likely to be hospitalized in an academic facility compared to privately insured patients.…”
Section: Discussionmentioning
confidence: 99%
“…This discordance in care by facility type is important as numerous studies have shown that access to academic facilities is limited and is dependent on race/ethnicity, median income, insurance type, and geographic location 32,33 . In a multivariable regression study utilizing hospital discharge records, Tikkanen et al 34 showed that Black patients were 2‐3 times less likely to be hospitalized in an academic facility compared to White patients. Additionally, uninsured patients were five times less likely to be hospitalized in an academic facility compared to privately insured patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 Adult black patients in New York City were 2 to 3 times less likely than white patients to be treated at academic medical centers, while minority patients in Boston were overrepresented at academic medical centers. 35 Jha and colleagues 10 found that the lowest-quality, highest-cost hospitals in the United States, primarily located in the south, cared for twice the proportion of elderly black patients compared with the highest-quality, lowest-cost hospitals. Dimick and colleagues 11 found that adult black surgical patients who lived in racially segregated health care service areas or markets were significantly more likely to receive care at lower-quality hospitals even if they lived closer to higher-quality hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Esses dados são necessariamente históricos, assim, se a I.A. precisa estudar os casos das últimas décadas para definir a expectativa de vida e cura de um paciente, o que acontece se a diferença racial provocou uma diferença no tratamento 18 e esse seja um dos fatores determinantes da morte prematura? O algoritmo que não foi especialmente criado para discriminar acaba por realizar esse tipo de ação, agora em virtude dos dados recebidos, não de sua programação.…”
Section: O Risco Inerente De Dados Tendenciosos Usados Para Treinar a Iaunclassified